Study of 3-D velocity structure characteristics in Dadu river Houziyan reservoir area at different impoundment stages - Yang, Zhenggang; Cao, Junxing; Wu, Yuchuan; Qin, Juan; Huang, Huibao; Du, Xingzhong; Yang, Mingxing; Wu, Jianchao (Frontiers in Earth Science, 2024)
High-resolution three-dimensional VP、VS and VP/VS images in the Houziyan Reservoir Area were obtained by using Fast Marching Tomography Package (FMTOMO) with the travel time data from 6330 seismic events monitored by the Houziyan Reservoir Seismic Network. This analysis yielded the 3-D velocity structure, including longitudinal wave velocity (VP), shear wave velocity (VS), and the ratio of longitudinal and shear wave velocity (VP/VS) at different impoundment stages. The data changes at various impoundment times, depths of sections, and directions of profiles were analyzed to obtain these results. The final findings demonstrate the following results: (1) Through tomographic analysis, it was determined that the underground velocity structure in the Houziyan reservoir area was anisotropic before impoundment. (2) The area of high wave velocity increases in stage 1,stage 3 and stage 4.The area of low wave velocity increases in stage 2, especially in depth, indicating significant changes in the underground velocity structure at different impoundment stages. (3) Compared to the changes in underground velocity structures in other reservoirs after impoundment, the Houziyan reservoir exhibited a unique pattern. ( 4) In general, the underground velocity structure displayed an overall increasing trend after impoundment. However, it also exhibited instances of decreasing velocity, reflecting continuous dynamic adjustments to the underground velocity structure after impoundment. These conclusions highlight the impact of impoundment in the reservoir area on the underground velocity structure and provide scientific theoretical support for seismic risk assessment following impoundment in the reservoir area.